A Review on Computational Fluid Dynamics Simulations of Industrial Amine Absorber Columns for CO2 Capture. Issue 1 (30th November 2022) - Jamali, Mohammad; Azari, Ahmad
Abstract: CO2 emission is an important environmental issue leading to global climate change, notably an increase in global temperatures; therefore, it is so imperative to reduce CO2 emissions to the atmosphere. Absorption columns using amine‐based solutions are a promising approach for CO2 removal from industrial gas streams. Many modeling and simulation research have been performed on CO2 absorption columns in which computational fluid dynamics (CFD) strategy is very appropriate and well‐known. As CFD modeling and simulation is a fast‐developing method, the most recent review papers do not include the core research in this field of study. In this study, numerical simulations of CO2 absorption columns using CFD strategy have been carried out applying various types of amine‐based solutions. Furthermore, the effect of various types of packing mesh generation on the absorption columns' efficiency was studied. Investigation of synergetic influence such as application of various nanoparticles in different amine‐based solutionsand activators, double diameter packed bed absorption columns with different packings, rotating packed columns with double diameter are proposed for future studies. Abstract : In this review, numerical simulations of CO2 absorption columns using a computational fluid dynamics (CFD) strategy were carried out applying various types of amine‐based solutions. The governing equations, different simulation models, mass transfer efficiency, and hydrodynamic properties including pressure drop and liquid holdup were studied as effective parameters.